Improvement of Blood Glucose, Serum Antioxidant Status and Liver Enzyme Changes by Hydroalcoholic Extract of Solanum melongena Green Cap in Diabetic Rats - Fatemeh Khazaei; Elham Ghanbari; Ali Rezvani; Somayeh Ghanbari; Mozafar Khazaei (Iranian Society of Pharmacognosy, 2020)
Background and objectives: Diabetes is associated with a wide range of disorders including oxidative stress. Solanum melongena L.  possessesantioxidant compounds and was introduced as an antidiabetic herb in Asian traditional texts. The aim of the present study was to investigate the effect of hydroalcoholic extract of S. melongena green cap on blood glucose and antioxidant status of liver in diabetic rats. Methods: In this experimental study, the extract was prepared by maceration method and 42 male Wistar rats (190-220 g) were divided into 6 groups (n=7/groups) including: 1. Control; 2. diabetic groups receiving 1 mL distilled water daily; groups 3 and 4 of normal rats receiving 100 and 200 mg/kg extracts, respectively, and diabetic treated groups 5 and 6 with 100 and 200 mg/kg extract, respectively. Diabetes was induced by intraperitoneal injection of streptozotocin (55 mg/kg). At the end of study, serum levels of fasting blood glucose (FBG), aspartate aminotransferase (AST), alanine aminotransferase (ALT), alkaline phosphatase (ALP), total protein, nitric oxide (NO) level and total antioxidant capacity (FRAP) were measured. Histological changes of liver were also assessed using hematoxylin and eosin staining. Results:Treatment of diabetic animals with the extract of S. melongena cap (100 and 200 mg/kg) significantly reduced serum levels of FBG, ALT, ALP, NO (p <0.001) and AST (p=0.017), while total protein (p <0.001) and FRAP (p=0.007) levels increased significantly. The extract also improved the liver tissue changes induced by diabetes. Conclusion:Solanum melongena cap is effective in improving liver complications and serum antioxidant status in diabetic rats.